Effect of Benzalkonium Chloride Adaptation on Sensitivity to Antimicrobial Agents and Tolerance to Environmental Stresses in Listeria monocytogenes - Yu, Tao; Jiang, Xiaobing; Zhang, Yige; Ji, Shengdong; Gao, Wujun; Shi, Lei (Frontiers in microbiology, 2018)
is an important food-borne pathogen that can persist in food processing environments and thus contaminate food products. Benzalkonium chloride (BC) is a common disinfectant widely used in food industry. Selective pressure associated with exposure to BC may result in adaptation to this agent in . In this study, the effect of BC adaptation on susceptibility to antimicrobial agents and tolerance to environmental stresses, as well as the role of efflux pumps in BC adaptation were investigated in . Exposure of to progressively increasing concentrations of BC led to adaptation not only to BC but also to several other antimicrobial agents with different modes of action, including cefotaxime, cephalothin, ciprofloxacin, and ethidium bromide (EtBr), indicating that the disinfectant BC has the ability to select for antibiotic resistance. Reserpine, an efflux pump inhibitor, reduced minimum inhibitory concentrations (MICs) of cephalosporins, ciprofloxacin, and EtBr in BC adapted strains, indicating that efflux pumps are involved in cross-adaptation to these antimicrobial agents. Our results showed that expression levels of the efflux pump MdrL in the BC adapted strains increased significantly relative to the corresponding wild-type strains ( < 0.05), with the highest increase in one BC adapted strain named HL06BCA. Moreover, the knockout mutant HL06BCAΔ showed impaired growth compared to that of HL06BCA when exposed to 2 μg/ml of BC. It suggests that efflux pump MdrL is associated with BC adaptation in . However, we did not find to be associated with cross-adaptation to cephalosporins, ciprofloxacin, and EtBr in HL06BCA. Additionally, increased sensitivity to acid, alkali, osmotic, ethanol, and oxidative stresses was observed in most strains after repeated exposure to BC. These results suggest rotation of different disinfectant is helpful to maintain high effectiveness of BC toward and ethanol and hydrogen peroxide are at least the appropriate candidates.